HAWC J2227+610 and Its Association with G106.3+2.7, a New Potential Galactic PeVatron - Albert, A.; Alfaro, R.; Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; et al. (Astrophysical Journal Letters, 2020)
We present the detection of very-high-energy gamma-ray emission above 100 TeV from HAWC J2227+610 with the High-Altitude Water Cherenov Gamma-Ray Observatory (HAWC) observatory. Combining our observations with previously published results by the Very Energetic Radiation Imaging Telescope Array System (VERTIAS), we interpret the gamma-ray emission from HAWC J2227+610 as emission from protons with a lower limit in their cutoff energy of 800 TeV. The most likely source of the protons is the associated supernova remnant G106.3+2.7, making it a good candidate for a Galactic PeVatron. However, a purely leptonic origin of the observed emission cannot be excluded at this time.
CRIS-Team Scopus Importer:2020-07-10